1976
DOI: 10.1111/j.1399-0004.1976.tb00049.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical variability in Sanfilippo B disease: a report on six patients in two related sibships

Abstract: Two closely related sibships are described in which six definite and two probable patients with Sanfilippo B disease were found. The wide variation in phenotypic expression in these patients is suggestive of a genetic background effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 11 publications
(4 reference statements)
1
4
0
Order By: Relevance
“…This was previously reported in other studies on Dutch patients with MPS IIIB (Moog et al 2007; van de Kamp et al 1976; Verhoeven et al 2009). Patients with the classical severe phenotype of MPS III become completely dependent on external care and fully wheelchair dependent during their teenage years and usually die within the first two decades of life.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This was previously reported in other studies on Dutch patients with MPS IIIB (Moog et al 2007; van de Kamp et al 1976; Verhoeven et al 2009). Patients with the classical severe phenotype of MPS III become completely dependent on external care and fully wheelchair dependent during their teenage years and usually die within the first two decades of life.…”
Section: Discussionsupporting
confidence: 83%
“…These 12 patients have been previously reported (Moog et al 2007; van de Kamp et al 1976, 1981; van Schrojenstein-de Valk and van de Kamp 1987). …”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…The gene encoding for NAGLU is localized on chromosome 17q21.1 (Zhao et al 1996) and over 100 mutations in the NAGLU gene (HGNC: 7632) have been identified (van de Kamp et al 1976; Beesley et al 1998, 2004, 2005; Schmidtchen et al 1998; Zhao et al 1998; Bunge et al 1999; Weber et al 1999; Esposito et al 2000; Tessitore et al 2000; Emre et al 2002; Chinen et al 2005; Champion et al 2010; Valstar et al 2010a; Ouesleti et al 2011; Selmer et al 2012; Tang et al 2013). Due to this large allelic heterogeneity, establishing a genotype-phenotype correlation is difficult.…”
Section: Introductionmentioning
confidence: 99%